2014
DOI: 10.1371/journal.pone.0105635
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin/Apolipoprotein J Attenuates Angiotensin II-Induced Renal Fibrosis

Abstract: The blockade of angiotensin II (Ang II) is a major therapeutic strategy for diabetic nephropathy. The main roles of Ang II in renal disease are mediated via the Ang type 1 receptor (AT1R). Upregulation of clusterin/apolipoprotein J has been reported in nephropathy models, suggesting it has a protective role in nephropathogenesis. Here, we studied how clusterin acts against Ang II-induced renal fibrosis. Levels of AT1R and fibrotic markers in clusterin-/- mice and Ang II infused rats transfected with an adenovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Therefore, our present results suggest the possible role of clusterin in renal function although eGFR was only mildly decreased. In support of our results, previous studies have shown the protective role of clusterin in Ang II‐induced renal fibrosis, ischemia‐reperfusion renal injury, chronic glomerular kidney disease of aging, and obesity‐induced kidney damage . Additionally, subgroup analysis in our studies showed that participants in the highest clusterin tertile had an increased OR for PCAD, especially in people with eGFR<90 mL/min/1.73 m 2 and Urea<7.14 mmol/L.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, our present results suggest the possible role of clusterin in renal function although eGFR was only mildly decreased. In support of our results, previous studies have shown the protective role of clusterin in Ang II‐induced renal fibrosis, ischemia‐reperfusion renal injury, chronic glomerular kidney disease of aging, and obesity‐induced kidney damage . Additionally, subgroup analysis in our studies showed that participants in the highest clusterin tertile had an increased OR for PCAD, especially in people with eGFR<90 mL/min/1.73 m 2 and Urea<7.14 mmol/L.…”
Section: Discussionsupporting
confidence: 92%
“…Improved clearance was associated with decreased levels of fibronectin, a heparan sulphate proteoglycan that has been shown to accelerate the aggregation of Aβ in vitro and contribute to the development of CAA in vivo . Although more work is needed to determine how clusterin contributes to clearance of Aβ via IPAD pathways, clusterin has been shown to contribute to the production and maintenance of the basement membrane and regulates the differentiation of vascular smooth muscle cells , which contribute to the motive force that drives IPAD .…”
Section: Discussionmentioning
confidence: 99%
“…However, the biological importance of CLU for the kidney is not fully understood. We and others have been investigating the biological impacts of CLU deficiency on adult kidneys using CLU knockout (KO) mice compared to CLU-expressing wild type (WT) control mice, and have demonstrated: (i) CLU KO in aging mice results in developing progressive glomerulopathy that is associated with glomerular antibody deposition [ 30 ]; (ii) CLU KO mice exhibit the higher levels of renal fibrosis in response to ureteral obstruction [ 31 ] or angiotensin II stimulation [ 32 ]; and (iii) our group has shown that CLU KO results in more severe renal IRI [ 26 ], in an experimental model of ischemic AKI, and also impairs renal repair after IRI [ 33 ]. However, the role of CLU in the progression to CKD from AKI has not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%